RELATIONSHIP OF BODY MASS INDEX WITH HbA1c MEASURES IN PATIENTS AT PRIMA MEDIKA DENPASAR HOSPITAL - S.A.N Diah Ratnasari Warassaty; Didik Prasetya; Nyoman Sudarma (PT. Jurnal Center Indonesia Publisher, 2025)
The rising prevalence of obesity in Indonesia contributes to increased risk of metabolic diseases such as diabetes mellitus. Body Mass Index (BMI) is commonly used to assess nutritional status and may be correlated with long-term blood glucose levels measured by Hemoglobin A1c (HbA1c). This study aimed to explore the relationship between BMI and HbA1c levels in patients at Prima Medika General Hospital, Denpasar. A cross-sectional analytic observational design was employed, involving 30 purposively selected respondents. BMI was calculated from weight and height measurements, while HbA1c levels were assessed using the immunoturbidimetric method. Results showed an even distribution of respondents in the normal and overweight BMI categories (each 46.5%), while 50% had HbA1c levels >8%. However, Pearson correlation analysis indicated no statistically significant relationship between BMI and HbA1c levels (p=0.982; r=-0.004). The study concludes that BMI does not have a linear correlation with HbA1c levels. Other factors such as type and duration of therapy, disease progression, and patient adherence may play a greater role in influencing glycemic control and should be further investigated.